A cadaveric study on the course and relations of the lingual nerve - Raniprabha S; Serin Peter (Asian Journal of Medical Sciences, 2025)
Background: The lingual nerve (LN) arises as a branch of the posterior division of the mandibular nerve in the infratemporal fossa, in front of the inferior alveolar nerve (IAN). It passes anteriorly near the mandibular lingual alveolar crest and appears on the side of the tongue resting on the hyoglossus. Finally, it winds around the submandibular duct (SMD) from lateral to medial side. LN was found damaged in 89% of paresthesia cases after the IAN block. The nerve can be injured during third molar tooth extraction, and during surgery in the submandibular region. Hence, understanding the relations of the nerve help to avoid injury. Aims and Objectives: To study the relation of LN with the IAN at their origin, the lower 3rd molar tooth, and the SMD. Materials and Methods: A cross-sectional cadaveric study was conducted in the Department of Anatomy, Government Medical College Kottayam for 6 months on 40 head and neck specimens. Results: The average anteroposterior distance between the nerves at the level of mandibular foramen was found to be 0.57 cm with Range 0.1 cm–1 cm. The average vertical distance between the poster part of the alveolar crest of the lower 3rd molar and the LN was 0.88 cm. In 22% of specimens, the nerve ran on the retromolar mandibular surface. In 95.45% of specimens triple relation was observed between LN and SMD. Conclusion: A thorough knowledge of the relations of LN will help clinicians to avoid injury during surgeries and nerve blocks.